The Role of Applying Business Ethics Principles in Operational Management - Imam Wibowo (Jurnal Komputer Indonesia (Ju-Komi), 2023)
Business ethics, as moral norms in a business context, have an important role in shaping sustainable and responsible operational management practices. This research aims to investigate the impact of implementing business ethics on the efficiency and sustainability of operational management in an organization. This research uses a qualitative approach with descriptive methods. The research results show that the application of business ethics principles in operational management is very important in establishing sustainable, responsible and ethical business practices. Principles such as honesty, autonomy, mutual benefit, justice and moral integrity are the main guidelines that shape the values, norms and behavior of employees and company leaders. The application of business ethics in operational management plays a role in creating an ethical work environment, ensuring quality products or services, strengthening relationships with stakeholders, reducing risks, and supporting corporate social responsibility (CSR). By incorporating business ethics into its operational management structure, companies not only comply with rules and regulations, but also create sustainable added value for all stakeholders, build strong relationships, and have a positive impact on society and the environment.